Integrated approach to study river fluxes, water and sediment sources apportionment in sparsely monitored catchment - S. Chalov; P. Terskii; T. Pluntke; L. Efimova; V. Efimov; V. Belyaev; A. Terskaia; M. Habel; D. Karthe; C. Bernhofer (Proceedings of the International Association of Hydrological Sciences, 2019)
The paper presents an integrated approach for the apportionment of water and sediment sources and pathways in ungauged territories. The approach comprises various elements such as a large-scale semi-distributed hydrological and erosion model (using the SWAT tool), a statistical assessment of regular discharge data, the discrimination of runoff sources using end-member mixing analysis (EMMA), the apportionment of sediment sources using fingerprinting technique and sediment concentration and water discharge hysteresis rating curves analyses. The approach has been applied to Western Dvina River Basin (WDRB). The results discussed in the paper indicate main features of the water and sediment regime. The components of the presented framework provide a guide for detailed water and sediment studies making it an inexpensive way to develop a roadmap to understand important hydrological processes at a watershed scale.